REGULARITIES OF DISTRIBUTION OF RESOURCES IN THE OIL AND GAS BEARING BASINS OF THE NORTH-AMERICAN PLATFORM - Ponomarenko, G.S. (Institute of Geological Sciences, NAS of Ukraine, 2014)
The assessment of the state of the hydrocarbon resource base is carried out for the Western Inner and Permian Oil-and-Gas Bearing Basins (OGBBs) of the North-American Platform is carried out for the further comparative analysis with OGBBs of the East-European Platform, in part with theDnieper-Pripyat OGBB.